2010
DOI: 10.1071/ch10007
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Activity of the Leaf-Specific Cyclotide vhl-2

Abstract: Cyclotides are plant-derived macrocyclic peptides with potential applications in the pharmaceutical and agricultural industries. In addition to their presumed natural function as host-defence peptides arising from their insecticidal activity, their other biological activities include antimicrobial, haemolytic, and cytotoxic activities, but at present, only limited information is available on the structural and chemical features that are important for these various activities. In the current study, we determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
2
3
Order By: Relevance
“…This observation is not supported by the results in the present study, where kB1 and kB2 that have different hydrophobicities show similar EC50 values. Contrary to the findings of Daly et al [36], the most hydrophilic cyclotide of the three cyclotides studied in the present study (cyO2) is the most potent of the three. However, the bracelet family, of which cyO2 is a member, was not included in the study of Daly et al [36].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…This observation is not supported by the results in the present study, where kB1 and kB2 that have different hydrophobicities show similar EC50 values. Contrary to the findings of Daly et al [36], the most hydrophilic cyclotide of the three cyclotides studied in the present study (cyO2) is the most potent of the three. However, the bracelet family, of which cyO2 is a member, was not included in the study of Daly et al [36].…”
Section: Discussioncontrasting
confidence: 82%
“…Contrary to the findings of Daly et al [36], the most hydrophilic cyclotide of the three cyclotides studied in the present study (cyO2) is the most potent of the three. However, the bracelet family, of which cyO2 is a member, was not included in the study of Daly et al [36]. In line with our results, Pränting et al [20] found cyO2 to be the most potent cyclotide of all the cyclotides tested, which included kB1 and kB2.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Cycloviolacin O32 GAPVCGETCFGGTCNTPGCTCDPWPVCTND M [112] Cycloviolacin O33 GLPVCGETCVGGTCNTPYCTCSWPVCTRD M [112] Cycloviolacin O34 GLPVCGETCVGGTCNTEYCTCSWPVCTRD M [112] Cycloviolacin O35 GLPVCGETCVGGTCNTPYCFCSWPVCTRD M [112] Cycloviolacin O36 GLPTCGETCFGGTCNTPGCTCDPFPVCTHD M [112] Viola hederacea Widely grown Cycloviolacin H1 GIPCGESCVYIPCLTSAIGCSCKSKVCYRN B [61,96] garden plant Cycloviolacin H2 AIACGESCVYIPCFIPGCSCRNRVCYLN B [113] Cycloviolacin H3 GLPVCGETCFGGTCNTPGCICDPWPVCTRN M [113] Cycloviolacin H4 GIPCAESCVWIPCTVTALLGCSCSNNVCYN B [114] Vhl-1 SISCGESCAMISFCFTEVIGCSCKNKVCYLN B [113] Vhl-2 GLPVCGETCFTGTCYTNGCTCDPWPVCTRN M [113,115] Vhr1 GIPCAESCVWIPCTVTALLGCSCSNKVCYN B [96] Viola pubescens Mt Tomah botanic gardens Vpub A GVIPCGESCVFIPCISAVIGCSCKSKVCYRN B [116] Vpub B GIIPCGESCVFIPCITSVVGCSCKSKVCYKN B [116] Vpub C GIIPCGESCVFIPCITSIVGCSCKSKVCYKN B [116] Viola arvensis Victorian Highlands Varv peptide A GLPVCGETCVGGTCNTPGCSCSWPVCTRN M [95,117] Melicytus angustifolius RBG, Melbourne Mang A GFPTCGETCTLGTCNTPGCTCSWPICTRD M [116] Melicytus chathamicus NSW and Norfolk Is Mech 1 GVIPCGESCVFIPCINKKKCSCKNKVCYRD B [118] Mech 2 GLPTCGETCTLGKCNTPKCTCNWPICYKD M [118] Mech 3 GLPTCGETCTLGKCNTPKCTCNWPICYKN M [118] Mech 4 GSIPCGESCVYIPCISSLLGCSCKSKVCYKD B [118] Mech 5 GVIPCGESCVFIPCISSVVGCTCKNKVCYRD B [118] Mech 6 GVIPCGESCVFIPCISSVVGCTCKNKVCYRN B [118] Mech 7 GIPICGETCTIGTCNTPGCTCSWPVCTRD M [118] Melicytus dentatus NSW and Victoria Mden A GIPTCGETCTLGTCNTPGCTCSWPICTKN M [116] Mden B GLPICGETCFTGKCYTPGCTCSYPICKKN M [116] Mden C GKPICGETCFKGKCYTPGCTCSYPVCKKN M [116] Mden E GIPCGESCVYIPCITAAIGCSCKSKVCYRN B [116] Mden F GLPICGETCFFGKCNTPKCTCINPICYKN M [116] Mden G GIPCAESCVYIPCITAALGCSCKNK...…”
mentioning
confidence: 99%
“…For example, structural analogues of the thaxtomin natural products have been synthesized and evaluated for phytotoxicity (Smith et al [8] ), and a new family of constrained azabicyclic homocholine analogues have been synthesized and evaluated for nicotinic acetylcholine receptor antagonist activity (McLeod et al [9] ). In contrast, a study of the subtleties of the threedimensional structure of vhl-2, a leaf-specific cyclotide, and its surface hydrophobicity has provided evidence for membrane binding and a relationship to haemolytic activity (Craik et al [10] ). The synthetic challenge associated with complex and novel structures is often sufficient to drive research programs and these efforts then make available larger quantities of material for biological studies.…”
mentioning
confidence: 99%